Analisa Vertical Lift Performance Pada Sumur “Af” Pada Lapangan “MP” Dengan Memperhitungkan Kehilangan Tekanan Pada Tubing Untuk Mendapatkan Laju Alir Optimal - Marsel Patempe; Mirza; Rohima Sera; Engilene Marlin; Joko Wiyono; Dody Finansa (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2021)
As is known, if an oil well is produced for a long time, the pressure will decrease so that it can reduce the production rate of the well. So it is necessary to do a vertical lift performance to determine the pressure loss in the tubing during production. Where in production it is important to determine the vertical lift performance in analyzing the pressure loss in the vertical pipe. Where the purpose of this study is to calculate the pressure loss in the tubing and also to obtain the optimal flow rate in the "AF" well in the "MP" field. There is a loss of pressure when the production stage has started, automatically the pressure in the reservoir will decrease to pwf, where after the fluid enters the tubing it starts to take into account the VLP value, where the liquid rate is the greater the pressure generated in the tubing will also be greater because of friction between the fluid and the tubing. so that the maximum oil flow rate is 167.61 Bopd, then the maximum water flow rate is 490.53 Bwpd, and the total maximum flow rate is 658.14 Bfpd. From the intersection of the VLP curve to the IPR curve, the optimal flow rate is 398 Bfpd.